Pedagogical Opportunities for Implementing an Individual Approach to the Initial Educational Process - Djamshitovna, Xaydarova Malika; Narzullayevich, Yo’ldoshev Bahodur (European Journal of Life Safety and Stability (2660-9630), 2021)
This article describes the pedagogical possibilities of implementing an individual approach to the primary education process, the factors influencing this process, based on the fact that the need to organize the primary education process on the basis of an individual approach is related to objective conditions. The article also discusses the specific advantages and disadvantages of organizing the primary education process on the basis of an individual approach.